Health-care professional and parental views and experiences of implementing infant feeding interventions: a qualitative evidence synthesis. (November 2018) - Toomey, Elaine; Byrne, Molly; Houghton, Catherine; Kelly, Colette; Matvienko-Sikar, Karen; McSharry, Jenny; Queally, Michelle; Doherty, Edel; Hayes, Catherine B; Hennessy, Marita; McHugh, Sheena; Kearney, Patricia M; et al.
Abstract: Background: Childhood obesity is an urgent global concern with a complex multifactorial aetiology. Infant feeding behaviours are a potential target for childhood obesity prevention. However, evidence for the effectiveness of interventions to improve infant feeding behaviours is inconsistent, and knowledge of how interventions have been implemented, what aspects work, and why, is lacking. This review aimed to synthesise qualitative evidence about parents' and health-care professionals' views and experiences of infant feeding interventions, and identify factors influencing intervention implementation. Methods: A systematic review and synthesis of qualitative evidence was conducted. CINAHL, Medline, PsycINFO, Embase, and SCOPUS were searched from database inception to Sept 25, 2017, for English-language qualitative studies reporting the implementation of infant feeding interventions from the perspectives of health-care workers, parents, or both. 4794 studies were screened using a-priori inclusion and exclusion criteria. Two reviewers independently extracted data and judged quality. A framework synthesis was conducted and GRADE-CERQual was used to assess confidence in findings. This review is registered with PROSPERO, number CRD42016039652. Findings: Of 4794 screened studies, 13 UK, US, and Australian-based studies were included. Supportive relationships and environments were integral to the successful implementation of infant feeding interventions for both health-care professionals and parents. Issues with capacity (ie, time and resources) negatively influenced implementation by health-care professionals; for parents, a focus on practical elements and sustainability beyond the intervention was crucial to ensure success. Interpretation: This review provides valuable information to enable informed and robust decisions about future infant feeding interventions and policy development, ensuring that these decisions are guided by stakeholder experiences and are cognisant of previous implementation challenges or successes. Methodologically, this study provides an innovative example of using qualitative evidence synthesis to explore factors influencing intervention implementation and engagement from both provider and participant perspectives. This review provides deeper insight into potential interactions between provider and participant experiences, and a comprehensive holistic overview of factors that are important to consider for future infant feeding interventions. Funding: Health Research Board Interdisciplinary Capacity Enhancement Award 2015-1026.